Methods of quality evaluation of air filters used in ventilation systems - Jankowski, Tomasz (Instal, 2023)
In order to ensure adequate air quality in rooms, in particular in urbanized areas, proper air purification on air filters in ventilation units of buildings is required. In general, both ventilation systems and in filtration and ventilation devices, the elements determining the quality of air extracted from or supplied to rooms are single – or multi-stage filtration systems, determined by hygienic or technological requirements. It was proposed to use the index to assess the quality of air filters during use in ventilation units of buildings.